PWE-311 Extra-levator abdomino-perineal resection for low rectal cancer. (22nd June 2015) - Tudor, E; Oliphant, Z; Marshall, M; Worrall, C; Mackey, P; Hunt, L; Edwards, T
Abstract : Introduction: Extra-levator abdomino-perineal resection (eLAP) has superseded standard abdomino-perineal excision (APER) for low rectal cancer. Reduction in rates of circumferential resection margin (CRM) involvement and tumour perforation offer improved oncological outcome. There is no consensus regarding management of the larger perineal defect that results. We report outcomes following primary closure following an eLAP. Method: All eLAPs undertaken in a single centre over five years were identified. eLAP and primary closure is the local standard of care. A retrospective review recorded CRM involvement, primary wound healing and infection rates, the incidence of perineal herniae, and subsequent intervention if required. Results: Fifty-one patients were identified, with a mean age of 70.2, and a male preponderance of 63%. Ten patients were classified ASA 3 (19.6%); the remainder were ASA 1–2. Thirty-two patients had a laparoscopic operation (63%), with a further 6 converted to open (12%). 14 patients had an open operation (27%). 38/51 patients (75%) had a clear CRM. There were no tumour perforations. EMVI was present in 13 patients (25%). Wound healing problems were identified in 12 patients (24%), with 6 requiring intervention (12%). The incidence of perineal hernia was 9/51 (18%) of which 5 (9.8%) were repaired surgically. Conclusion: This series suggests that eLAP combined with primary closure of the perineum may offer the benefits of low rates of CRM involvement and tumour perforation yet minimal perineal wound related morbidity compared to published data. Disclosure of interest: None Declared.